2018
DOI: 10.3390/min8120561
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in the Application of Carbon-Bearing Materials in Blast Furnace Iron-Making

Abstract: The iron and steel industry is still dependent on fossil coking coal. About 70% of the total steel production relies directly on fossil coal and coke inputs. Therefore, steel production contributes by ~7% of the global CO2 emission. The reduction of CO2 emission has been given highest priority by the iron- and steel-making sector due to the commitment of governments to mitigate CO2 emission according to Kyoto protocol. Utilization of auxiliary carbonaceous materials in the blast furnace and other iron-making t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Solid based reduction processes are much more effective in the processing of zincbearing by-products. Common reductant sources include coke breeze, pulverized coal, and carbon-bearing revert material such as blast furnace dust (Ahmed 2018). Table 3 compares gas direct reduction and solid fuel direct reduction to conventional blast furnace pig iron production.…”
Section: Pyrometallurgical Separation Techniquesmentioning
confidence: 99%
“…Solid based reduction processes are much more effective in the processing of zincbearing by-products. Common reductant sources include coke breeze, pulverized coal, and carbon-bearing revert material such as blast furnace dust (Ahmed 2018). Table 3 compares gas direct reduction and solid fuel direct reduction to conventional blast furnace pig iron production.…”
Section: Pyrometallurgical Separation Techniquesmentioning
confidence: 99%
“…Such composites are very attractive to the aspects of energy saving and environmental protection. The studies carried out on iron ore-carbon composite have demonstrated higher reduction rate and lower coke consumption compared to the ordinary burden materials [47][48][49][50][51][52]. It was demonstrated that the starting temperature of carbon solution-loss reaction (Boudouard reaction) decreased as the degree of contact between iron ore and carbonaceous material increased [52,53].…”
Section: Cold Bonded Briquettes and Pre-reduced Agglomeratesmentioning
confidence: 99%
“…The steel demand is anticipated to reach 1.5 times more than the present levels by 2050 to meet the demands of an increasing population [2]. Approximately 70% of crude steel depends on fossil fuel, such as coke [3]. The amount of CO 2 emitted by steelmaking factories was around 2.3 billion tons in 2007, while it is predicted to reach about 3.0 billion tons by 2050 [4].…”
Section: Introductionmentioning
confidence: 99%